Gutenberg und die Zukunft der Betriebswirtschaftslehre - Horst Albach (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
Im ersten Teil wird die Theorie der Unternehmung von Erich Gutenberg in ihren Grundzügen dargestellt. Dabei wird auf den Kombinationsprozeß als das theoretische Kernstück, in dem alle betrieblichen Teilbereiche integriert sind, besonders eingegangen. Die in der Theorie Gutenbergs offen gebliebenen Fragen werden behandelt: Das Investitionsproblem, das Oligopolproblem und das Interessenproblem. Die Antworten auf das Interessenproblem werden die Zukunft der Betriebswirtschaftslehre bestimmen. Folgt sie den Ansätzen der Kontrakttheorie, die moral hazard zur Grundvoraussetzung der menschlichen Zusammenarbeit im Betrieb macht, wird die Betriebswirtschaftslehre eine Konflikttheorie sein. Folgt sie dem Ansatz Gutenbergs unter Einbezug organisatorischer Maßnahmen, die die Grundvoraussetzung des Vertrauens absichern, dann wird die zukünftige Betriebswirtschaftslehre eine Harmonietheorie sein. – – The first part deals with the theory of the firm by Erich Gutenberg. The process of combining factors of production in a production technology to produce marketable products is the corner stone of that theory which integrates all the different functional areas of the firm under this concept. The paper then turns to the open questions in Gutenberg's theory of the firm: the investment problem, the oligopoly problem, and the problem of conflicting interests. If conflicting interests and the resulting distrust of cooperative behavior of the members of the firm is made the dominant feature of a future theory, with moral hazard being at the center of theoretical interest, the character of the theory of the firm will be quite different from another possible scenario of theoretical development: if the firm is considered a social institution built on mutual trust and designed to reinforce that trust, then the theory of the firm will quite substantially differ from present contract theory. The importance of these two theoretical assumptions for the different functional areas of the firm and the partial theories explaining them is worked out.
Keywords: 330